Kväveomsättning i gräsmark med olika artantal och artsammansättningar - Sanfridsson, Anna-Carin (2005)
This study was carried out at the Swedish University of Agricultural Sciences, Dept. of Agricultural Research for Northern Sweden. The aim of the study was to determine how plant species richness and diversity influence the nitrogen pools and nitrogen fluxes in the soil. Plant and soil samples from a biodiversity experiment in grasslands were used. Thirty plots with 12 grassland plant species (legumes, grasses, and non-legume herbs), combined from 1-12 species were investigated. The aboveground biomass was harvested in mid-August 2002. In late October the soil was sampled and collected for analyses in the laboratory.